2008
DOI: 10.1016/j.amepre.2007.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Recreational Resources in Minority and Low Socioeconomic Status Areas

Abstract: Recreational facilities and the resources they offer are not equitably distributed. The presence of parks in poor and minority areas suggest that improving the types and quality of resources in parks could be an important strategy to increase physical activity and reduce racial/ethnic and socioeconomic disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
316
2
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(346 citation statements)
references
References 36 publications
16
316
2
12
Order By: Relevance
“…The present findings are similar to a study in California which found that there were more places to engage in PA in low SES areas (25). Other researchers have reported no discrepancies in park availability between areas of differing SES (24,35,36), but there is an equally substantial body of evidence documenting fewer parks in lower income areas (17)(18)(19)(20)(21)(22). In KCMO, our findings might be explained by the fact that low income and diverse populations are generally found within the older, urban core of the city (Figure 1).…”
Section: Park Availabilitysupporting
confidence: 88%
See 2 more Smart Citations
“…The present findings are similar to a study in California which found that there were more places to engage in PA in low SES areas (25). Other researchers have reported no discrepancies in park availability between areas of differing SES (24,35,36), but there is an equally substantial body of evidence documenting fewer parks in lower income areas (17)(18)(19)(20)(21)(22). In KCMO, our findings might be explained by the fact that low income and diverse populations are generally found within the older, urban core of the city (Figure 1).…”
Section: Park Availabilitysupporting
confidence: 88%
“…For race/ethnicity, we identified the percentage of minority residents, defined as non-White and Hispanic White persons, and tracts were again categorized into even tertiles (low, medium, and high percent minority). For both income and percent minority, tracts were grouped into categories in order to ease interpretation between high versus medium versus low income or percent minority areas and to maintain consistency with most past studies exploring similar issues (17,19,20,(22)(23)(24)(25)(26)(27).…”
Section: Census Tract Income and Race/ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Historical policies of social exclusion as well as documented discrimination in access to health‐enhancing resources experienced by racial/ethnic minority groups in the United States are likely contributors to racial/ethnic differences in CVH 16, 17, 18. For example, neighborhoods with a higher percentage of racial/ethnic minority residents—regardless of income—have fewer grocery stores,19 fewer recreation facilities,20 and less walkability21; these neighborhood resources have been linked to preservation of ideal CVH 22. Previous research has shown that individuals who have multiple forms of social disadvantage—such as low income, low education, and nonwhite race—are even less likely to have ideal CVH 11.…”
Section: Discussionmentioning
confidence: 99%
“…2 While physical activity (PA) improves overall health by lowering the risk for obesity and its related ailments, 3 most Americans fall short of current PA guidelines. 4 Recent studies show that the built environment plays an important role in promoting PA. [5][6][7][8][9][10] However, neighborhoods with low-income, minority residents often have low walkability as a result of busy streets; 11,12 absent or poorly maintained sidewalks, crosswalks, and parks; [13][14][15] and actual or perceived threats to personal safety. 16,17 Thus, individuals from these neighborhoods often have limited access to PA facilities and may have a higher risk of developing obesity.…”
Section: Introductionmentioning
confidence: 99%